The Perceptions Of Novice EFL Teachers On Addressing Comprehension Issues In Students’ Reading - Herman Resyadi; Basri, Nurfajriah; Syam, Ferawaty (P3M Politeknik Negeri Media Kreatif, 2025)
The main concern of this research is to expose the Perceptions of Novice EFL Teachers on Addressing Comprehension Issues in Students’ Reading in junior high school setting. The research objective is to figure out the strategies of novice EFL teachers use to help students overcome reading comprehension issues. Qualitative research used as the research method with the case study design, involving two novice EFL teachers with advanced level and fewer years of experiences. Interview was used as the main instrument of this research, and Interactive Model by Miles and Huberman was also used as the technique of data analysis. The findings of this research expose that the novice EFL teachers face challenges in addressing students reading comprehension issues due to limited experiences and training. Despite these obstacles, they adapt by using strategies like pre-reading activity and vocabulary support. This highlights the need for targeted professional development to better equip novice EFL teacher in supporting students’ comprehension.